Prenatal Folic Acid Supplements and Reduced Risk of Severe Language Delay - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
The prospective Norwegian Mother and Child Cohort Study of pregnant women between 1999 and 2008 was used by researchers at the Norwegian Institute of Public Health, Oslo to examine the association between mothers' use of prenatal folic acid supplements and risk of severe language delay in the children at age 3 years.